New composite sustainability indices for the assessment of a chemical process in the conceptual design stage: case study on hydrogenation plant. (15th June 2016) - Ordouei, Mohammad Hossein; Elsholkami, Mohamed; Elkamel, Ali; Croiset, Eric
Abstract: Sustainability indices are increasingly recognized as a powerful tool for assessing the performance of chemical process designs considering energy, environment, safety and technological improvement aspects and above all, economy. Sustainability indicators enable decision makers to simplify, quantify and analyze complex information. Generally, it is challenging to evaluate the performance of process designs on the basis of a large number of indicators. The integration of a set of key sustainability indicators in the form of a composite index is essential for simplifying the evaluation of sustainability performance. Currently available methodologies for sustainability assessment of process designs require detailed process data, which are typically unavailable at the conceptual design phase. This paper introduces a new composite sustainability index ( CSI ) that addresses the sustainability performance of chemical processes and which can be applied for early design phases where minimum amount of data are available. The three pillars of sustainability are considered in the development of the new composite index, which are energy, environmental and safety aspects. A conceptual decision model based on the analytical hierarchy process can be employed to compare and determine weights for the different sustainability indicators, which are then aggregated to obtain the CSI, when the indicators conflict. The capability of the proposed model is investigated by applying it to a hydrogenation case study to choose the more sustainable design among different alternatives. Highlights: A new methodology was introduced which uses new sustainability quantification indices. The indices were used to design upgrading plants & found cleaner sustainable process. The above methodology ascertains sustainable processes without compromising economy. The methodology can be extended to biofuels/energy, product & process at design stage. The new methodology ranks processes based on safety, environmental & energy impacts.